2023
DOI: 10.3390/plants12071516
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Perilla frutescens (L.) Britt. Essential Oil and Its Main Component on Culex pipiens pallens (Diptera: Culicidae)

Abstract: Sustainable control of mosquitoes, vectors of many pathogens and parasites, is a critical challenge. Chemical insecticides are gradually losing their effectiveness because of development of resistance, and plant metabolites are increasingly being recognized as potential alternatives to chemical insecticides. This study aimed to analyze the main components of Perilla frutescens essential oil (PE-EO), investigate the specific activity of PE-EO as a botanical insecticide and mosquito repellent, and explore whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Controlling of egg hatching before larval emergence is another e cient approach for malarial vector management [32]. In the present study, the mean percentage hatchability of the eggs was observed post 72 h. It was found that the mean percentage hatchability was inversely proportional to the concentration of the essential oil.…”
Section: Ovicidal Activitymentioning
confidence: 47%
“…Controlling of egg hatching before larval emergence is another e cient approach for malarial vector management [32]. In the present study, the mean percentage hatchability of the eggs was observed post 72 h. It was found that the mean percentage hatchability was inversely proportional to the concentration of the essential oil.…”
Section: Ovicidal Activitymentioning
confidence: 47%
“…albopictus larvae with PCR EO, indicating its potential in the control of mosquitoes. Although the World Health Organization does not specify the effective concentration for larvicidal activity, one component with an LC 50 of less than 100 mg/L is generally considered active [37]. Based on the LC 50 , the toxicity of the main components in CRB EO toward mosquito larvae decreases in the order of D-limonene > p-cymene > γ-terpinene > methyl 2-(methylamino)benzoate > α-terpineol.…”
Section: Larvicidal Activity Of Crb Eo and Its Main Chemical Componentsmentioning
confidence: 99%
“…Due to resistance development, chemical insecticides are losing their effectiveness, and plant metabolites are gaining recognition as potential alternatives. Zhang et al [13] demonstrated that Perilla frutescens oil, including its main component, 2-hexanoylfuran, has insecticidal effects on Culex pipiens pallens mosquitoes, indicating its potential as a new plant-based biopesticide.…”
mentioning
confidence: 99%